Rate of thromboembolic and bleeding events in patients undergoing concomitant aortic valve surgery with left ventricular assist device implantation. (15th July 2022) - Yalcin, Yunus C.; Veenis, Jesse F.; Brugts, Jasper J.; Antonides, Christiaan F.J.; Veen, Kevin M.; Muslem, Rahatullah; Bekkers, Jos A.; Gustafsson, Finn; Tedford, Ryan J.; Bogers, Ad J.J.C.; Caliskan, Kadir
Abstract: Background: Significant aortic regurgitation at the time of left ventricular assist device (LVAD) implantation, requires concomitant aortic valve (AoV) replacement or repair. However, the impact of concomitant AoV surgery on morbidity remains unknown. Therefore, our aim is to determine the impact of concomitant AoV surgery on thromboembolic and bleeding events. Methods: A retrospective IMACS registry study, including patients implanted from 2013 until September 2017. Differences between different concomitant AoV surgery modalities were analyzed. Results: In total, 785 (5.1%) out of 15.267 patients (median age 58 IQR 49–66 years, 79% male) underwent concomitant AoV surgery (median age 63 IQR 54–69 years, 84% male); 386 (49%) patients received biological prostheses, 71 (9%) mechanical prostheses and 328 (42%) AoV repairs. In total, 54 (8%) patients with AoV surgery experienced a thromboembolic event and 1016 (9%) patients with no AoV surgery. Furthermore, concomitant AoV surgery was associated with an increased rate of all and nonsurgical bleedings. Following a multivariable Cox regression, concomitant AoV surgery remained an independent predictor for bleeding events. Conclusions: In LVAD patients undergoing concomitant AoV surgery, thromboembolic event rates were not higher, however both all and nonsurgical bleeding event rates were higher. Highlights: Concomitant aortic valve surgery is an independently risk factor associated with increased rate of bleeding following LVAD implantation. Concomitant aortic valve repair surgery is associated with an increased rate of pump thrombosis following LVAD implantation. Concomitant aortic valve surgery is not associated with an increased rate of hemorrhagic or ischemic stroke following LVAD implantation.